GOCE Gradiometer Measurement Disturbances and their Modelling by Means of Ionospheric Dynamics - Ince, Elmas Sinem (2017)
We examine the presence of residual non-gravitational signatures in gravitational gradients measured by GOCE Electrostatic Gravity Gradiometer. These signatures are observed over the geomagnetic poles during geomagnetically active days and contaminate the trace of the Gravitational Gradient Tensor by up to three to five times the expected noise level of the instrument (11 mE). We investigate these anomalies in the gradiometer measurements along many satellite tracks and examine possible causes by using external datasets, such as Interplanetary Electric Field observations from the ACE (Advanced Composition Explorer) and WIND spacecraft and Poynting flux (vector) estimated from Equivalent Ionospheric Currents derived from Spherical Elementary Current Systems over North America and Greenland. We show that the variations in the east-west and vertical electrical currents and Poynting flux (vector) components at the satellite position are highly correlated with the disturbances observed in the gradiometer measurements. We identify the relation between the ionospheric dynamics and disturbances and develop a data-driven model to reduce the effects of these disturbances. The results presented in this dissertation discover that the cause of the disturbances are due to intense ionospheric dynamics that are enhanced by increased solar activity which causes a dynamic drag environment. Moreover, using external information about the ionospheric dynamics, we successfully model and remove a high percentage of these disturbances for the first time in GOCE literature and promise improved data for future gravitational field models and studies of the Earth's upper atmosphere.